Entanglement-assisted quantum speedup: Beating local quantum speed limits - Yasmin, Farha; Sperling, Jan (Physical Review A)

Quantum walks and entanglement in cavity networks - Di Fidio, Christian; Ares, Laura; Sperling, Jan (Physical Review A)

Sub-cycle strong-field tunneling dynamics in solids - Yang, Shidong; Liu, Xiwang; Zhang, Hongdan; Song, Xiaohong; Zuo, Ruixin; Meier, Torsten; Yang, Weifeng (Optics Express)
Tunneling ionization is a crucial process in the interaction between strong laser fields and matter which initiates numerous nonlinear phenomena including high-order harmonic generation, photoelectron holography, etc. Both adiabatic and nonadiabatic tunneling ionization are well understood in atomic systems. However, the tunneling dynamics in solids, especially nonadiabatic tunneling, has not yet been fully understood. Here, we study the sub-cycle resolved strong-field tunneling dynamics in solids via a complex saddle-point method. We compare the instantaneous momentum at the moment of tunneling and the tunneling distances over a range of Keldysh parameters. Our results demonstrate that for nonadiabatic tunneling, tunneling ionization away from Γ point is possible. When this happens the electron has a nonzero initial velocity when it emerges in the conduction band. Moreover, consistent with atomic tunneling, a reduced tunneling distance as compared to the quasi-static case is found. Our results provide remarkable insight into the basic physics governing the sub-cycle electron tunneling dynamics with significant implications for understanding subsequent strong-field nonlinear phenomena in solids.

Optical Stark effect in type-II semiconductor heterostructures - Schäfer, F.; Trautmann, A.; Ngo, C.; Steiner, J. T.; Fuchs, C.; Volz, K.; Dobener, F.; Stein, M.; Meier, Torsten; Chatterjee, S. (Physical Review B)

Microscopic simulations of the dynamics of excitonic many-body correlations coupled to quantum light - Rose, Hendrik; Sharapova, Polina; Meier, Torsten
Dataset of the publication "Microscopic simulations of the dynamics of excitonic many-body correlations coupled to quantum light" H. Rose, P. R. Sharapova, and T. Meier, Proc. SPIE 12884, Ultrafast Phenomena and Nanophotonics XXVIII, 1288403 (2024). ( https://doi.org/10.1117/12.2690245 ). The zip file includes the data on which the plots shown in figures 1 and 2 are based.

Microscopic simulations of the dynamics of excitonic many-body correlations coupled to quantum light - Rose, Hendrik; Sharapova, Polina R.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVIII)

Time-bin entanglement in the deterministic generation of linear photonic cluster states - Bauch, David; Köcher, Nikolas; Heinisch, Nils; Schumacher, Stefan (APL Quantum)
We theoretically investigate strategies for the deterministic creation of trains of time-bin entangled photons using an individual quantum emitter described by a Λ-type electronic system. We explicitly demonstrate the theoretical generation of linear cluster states with substantial numbers of entangled photonic qubits in full microscopic numerical simulations. The underlying scheme is based on the manipulation of ground state coherences through precise optical driving. One important finding is that the most easily accessible quality metrics, the achievable rotation fidelities, fall short in assessing the actual quantum correlations of the emitted photons in the face of losses. To address this, we explicitly calculate stabilizer generator expectation values as a superior gauge for the quantum properties of the generated many-photon state. With widespread applicability in other emitter and excitation–emission schemes also, our work lays the conceptual foundations for an in-depth practical analysis of time-bin entanglement based on full numerical simulations with predictive capabilities for realistic systems and setups, including losses and imperfections. The specific results shown in the present work illustrate that with controlled minimization of losses and realistic system parameters for quantum-dot type systems, useful linear cluster states of significant lengths can be generated in the calculations, discussing the possibility of scalability for quantum information processing endeavors.

Organic Room-Temperature Polariton Condensate in a Higher-Order Topological Lattice - Bennenhei, Christoph; Shan, Hangyong; Struve, Marti; Kunte, Nils; Eilenberger, Falk; Ohmer, Jürgen; Fischer, Utz; Schumacher, Stefan; Ma, Xuekai; Schneider, Christian; Esmann, Martin (ACS Photonics)

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)
In the SUPER scheme (Swing-UP of the quantum EmitteR population), excitation of a quantum emitter is achieved with two off-resonant, red-detuned laser pulses. This allows the generation of high-quality single photons without the need of complex laser stray light suppression or careful spectral filtering. In the present work, we extend this promising method to quantum emitters, specifically semiconductor quantum dots, inside a resonant optical cavity. A significant advantage of the SUPER scheme is identified in that it eliminates re-excitation of the quantum emitter by suppressing photon emission during the excitation cycle. This, in turn, leads to almost ideal single-photon purity, overcoming a major factor typically limiting the quality of photons generated with quantum emitters in high-quality cavities. We further find that for cavity-mediated biexciton emission of degenerate photon pairs, the SUPER scheme leads to near-perfect biexciton initialization with very high values of polarization entanglement of emitted photon pairs. Published by the American Physical Society 2024

Topological edge and corner states in coupled wave lattices in nonlinear polariton condensates - Schneider, Tobias; Gao, Wenlong; Zentgraf, Thomas; Schumacher, Stefan; Ma, Xuekai (Nanophotonics)
Abstract Topological states have been widely investigated in different types of systems and lattices. In the present work, we report on topological edge states in double-wave (DW) chains, which can be described by a generalized Aubry-André-Harper (AAH) model. For the specific system of a driven-dissipative exciton polariton system we show that in such potential chains, different types of edge states can form. For resonant optical excitation, we further find that the optical nonlinearity leads to a multistability of different edge states. This includes topologically protected edge states evolved directly from individual linear eigenstates as well as additional edge states that originate from nonlinearity-induced localization of bulk states. Extending the system into two dimensions (2D) by stacking horizontal DW chains in the vertical direction, we also create 2D multi-wave lattices. In such 2D lattices multiple Su–Schrieffer–Heeger (SSH) chains appear along the vertical direction. The combination of DW chains in the horizonal and SSH chains in the vertical direction then results in the formation of higher-order topological insulator corner states. Multistable corner states emerge in the nonlinear regime.

Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research)
Exceptional points (EPs), with their intriguing spectral topology, have attracted considerable attention in a broad range of physical systems, with potential sensing applications driving much of the present research in this field. Here, we investigate spectral topology and EPs in systems with significant nonlinearity, exemplified by a nonequilibrium exciton-polariton condensate. With the possibility to control loss and gain and nonlinearity by optical means, this system allows for a comprehensive analysis of the interplay of nonlinearities (Kerr type and saturable gain) and non-Hermiticity. Not only do we find that EPs can be intentionally shifted in parameter space by the saturable gain, but we also observe intriguing rotations and intersections of Riemann surfaces and find nonlinearity-enhanced sensing capabilities. With this, our results illustrate the potential of tailoring spectral topology and related phenomena in non-Hermitian systems by nonlinearity. Published by the American Physical Society 2024

Novel Phosphazenium Tetrafluoroborate Dopant Enables Efficient and Thermally Stable n‐Doped Organic Semiconductors - Wei, Huan; Guo, Jing; Liu, Heng; Wu, Tong; Chen, Ping‐An; Dong, Chuanding; Wang, Shu‐Jen; Schumacher, Stefan; Bai, Yugang; Lei, Ting; Wang, Suhao; Hu, Yuanyuan (Advanced Electronic Materials)
Abstract Thermal stability is crucial for doped organic semiconductors (OSCs) and their applications in organic thermoelectric (OTE) devices. However, the capacity of n‐dopants to produce thermally stable n‐doped OSC films has not been thoroughly explored, with few reports of high thermal stability. Here, a novel n‐dopant, phosphazenium tetrafluoroborate (P 2 BF 4 ) is introduced, which effectively induces n‐doping in N2200, P(PzDPP‐CT2) and several other commonly used OSCs. Remarkably, the electrical conductivity of P 2 BF 4 ‐doped OSC films remains almost unchanged even after heating at temperatures > 150 °C for 24 h, far superior to the films doped with benchmark N‐DMBI. The exceptional thermal stability observed in P 2 BF 4 ‐doped P(PzDPP‐CT2) films allows for stable operation of the corresponding organic thermoelectric devices at 150 °C for 16 h, a milestone not previously achieved. This study offers valuable insights into the development of n‐dopants capable of producing OSCs with outstanding thermal stability, paving the way for the practical realization of OTE devices with enhanced operation stability.

Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.

Photochemical Reaction Enabling the Engineering of Photonic Spin–Orbit Coupling in Organic-Crystal Optical Microcavities - Liang, Qian; Ma, Xuekai; Gu, Chunling; Ren, Jiahuan; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (Journal of the American Chemical Society)

Understanding and Improving Triplet Exciton Transfer in Sensitized Silicon Solar Cells - Krenz, Marvin; Sanna, Simone; Gerstmann, Uwe; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Analyzing High-Order Harmonic Generation in Solids Based on Semi-Classical Recollision Models - Zhang, Hongdan; Zuo, Ruixin; Yang, Shidong; Trautmann, Alexander; Song, Xiaohong; Meier, Torsten; Yang, Weifeng (High-Order Harmonic Generation in Solids)

High-Order Harmonic Generation in Semiconductors with Excitonic Effects - Reichelt, Matthias; Zuo, Ruixin; Song, Xiaohong; Yang, Weifeng; Meier, Torsten (High-Order Harmonic Generation in Solids)

Floquet dynamics of ultracold atoms in optical lattices with a parametrically modulated trapping potential - Meier, Torsten; Ali, Usman; Holthaus, Martin

Ultrafast Electron Dynamics at the P‐rich Indium Phosphide/TiO2 Interface - Diederich, Jonathan; Rojas, Jennifer Velazquez; Paszuk, Agnieszka; Pour, Mohammad Amin Zare; Höhn, Christian; Alvarado, Isaac Azahel Ruiz; Schwarzburg, Klaus; Ostheimer, David; Eichberger, Rainer; Schmidt, Wolf Gero; Hannappel, Thomas; van de Krol, Roel; et al. (Advanced Functional Materials)
Abstract The current efficiency records for generating green hydrogen via solar water splitting are held by indium phosphide (InP)‐based photo‐absorbers, protected by TiO 2 layers grown through atomic layer deposition (ALD). InP is also a leading material for photonic integrated circuits and computing, where ultrafast near‐surface behavior is key. A previous study described electronic pathways at the phosphorus‐rich (P‐rich) surface of p‐doped InP(100) using time‐resolved two‐photon photoemission (tr‐2PPE) spectroscopy. Here, the intricate electron pathways of the P‐rich InP surface modified with ALD‐deposited TiO 2 are explored. Photoexcited bulk InP electrons migrate through a bulk‐to‐surface transition cluster of states and surface states and inject into the TiO 2 conduction band (CB). Energy levels and occupation dynamics of CB states in P‐rich InP and TiO 2 adlayers are observed, with discrete states preserved up to 10 nm TiO 2 deposition. Thermalization lifetimes of excited electrons > 0.8 eV above the InP conduction band minimum (CBM) are preserved for layer thicknesses up to 2.5 nm. Annealing at 300 °C to achieve crystalline TiO 2 reconstructions destroys interfacial states, affecting charge transfer. These observations enable innovative engineering of the P‐rich InP/TiO 2 heterointerface, opening new possibilities for studying hot‐carrier extraction, adsorbate effects, surface plasmons, and improving photovoltaic and PEC water‐splitting devices.